Pengaruh Lokasi dan Prosedur Kredit terhadap Keputusan Pengambilan Kredit pada Nasabah PT. BPR Kerta Arthamandiri Kota Kepanjen – Kabupaten Malang - Jevia Purnamasari; Sri Wilujeng; Zuhrotul Mufidah (Fakultas Ekonomika dan Bisnis Universitas PGRI Kanjuruhan Malang, 2019)
This study to determine the effect of location and credit procedures on credit decision making on customers of PT. BPR Kerta Arthamandiri Kepanjen city - Kabupaten. Malang. This type of research is quantitative research. The population in this study were all customers of PT. BPR Kerta Arthamandiri. The sample used from this study is that some customers of PT. BPR Kerta Arthamandiri. The data analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that the location variables and credit procedures simultaneously have a positive effect on credit decision-making for customers of PT. BPR Kerta Arthamandiri Kepanjen city - Kab. Poor. And partially credit procedures do not have a significant effect on credit decision making, while location has a significant effect on credit decision making on customers of PT. BPR Kerta Arthamandiri Kepanjen city - Malang District.